TERNOPIL REGION IN THE LIFE OF VASIL STEFANYK (TO 140-TH ANNIVERSARY FROM A WRITER’S BIRTHDAY) - Vynogradnyk, T. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article examines the “Ternopil ways” of Vasyl Stefanyk, discloses little-known biographical facts of the writer’s creative work.